Application of Artsteps in Exhibitions as a Creative Learning Platform for Art Education Students - Faradila, Nita Dian; Indar Sabri; Welly Suryandoko; Trisakti (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Art is a skill or medium that is done and made by humans to realize the imagination and creativity of the artist. Art has several fields such as dance, painting, sculpture, carving, and many more. Art includes many human activities in creating visual, audio, or performance works based on the imagination of the artist’s ideas and techniques of the art maker (artist). Art exhibition is an activity to exhibit or showcase works of art so that they can be appreciated by the general public with the aim of conveying creative ideas and ideas owned by the artist. This exhibition is carried out on the website artsteps.com. The website is a website that is useful for exhibiting works in the form of paintings that are famous in pandemic areas. Artsteps presents a 3D virtual exhibition platform where individuals and collectives can exhibit their work on the platform. This platform is useful in the implementation of exhibitions that are carried out to fulfill exhibition management courses, as well as useful for the general public or art education students in appreciating works of art virtually. In this research, the researcher conducted several qualitative approaches, namely interviews and observations. This research also has the aim of fostering the spirit of work to visitors to the virtual exhibition that has been implemented.